1996
DOI: 10.1038/sj.clpt.1996.365
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Neurokinin1 antagonist, CP-99,994, in comparison to ibuprofen and placebo in the oral surgery model.

Abstract: Clinical Pharmacology & Therapeutics (1996) 59, 216–216; doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…However, low doses of U-50,488H and U-69,593 themselves induced aversive effects as measured by conditioned place preference procedures (Shippenberg and Herz 1988;Suzuki et al 1992). In humans, these κ-opioid receptor agonists cause dysphoria and psychotomimetic syndrome (Peters and Gaylor 1989;Dionne et al 1991), while TRK-820 did not cause psychotomimetic effects (Endoh et al 2000). Previous study demonstrated that TRK-820 did not engender place preference or place aversion (Nagase et al 1998).…”
Section: Discussionmentioning
confidence: 91%
“…However, low doses of U-50,488H and U-69,593 themselves induced aversive effects as measured by conditioned place preference procedures (Shippenberg and Herz 1988;Suzuki et al 1992). In humans, these κ-opioid receptor agonists cause dysphoria and psychotomimetic syndrome (Peters and Gaylor 1989;Dionne et al 1991), while TRK-820 did not cause psychotomimetic effects (Endoh et al 2000). Previous study demonstrated that TRK-820 did not engender place preference or place aversion (Nagase et al 1998).…”
Section: Discussionmentioning
confidence: 91%
“…Single intramuscular injections of TRK-820 up to 30 mg are well tolerated by healthy volunteers, whereas a dose of 40 mg TRK-820 produces moderate behavioral/ psychological side effects, but not psychotomimetic activity (Toray Industries, Inc., unpublished data). Thus, TRK-820 was again shown to be different from other k -opioid receptor agonists, such as the arylacetamide spiradoline, which cause dysphoria and psychotomimetic reactions (5,6).…”
mentioning
confidence: 99%
“…[10]. However, a recent publication describes two placebocontrolled studies of the same compound in dental pain following oral surgery [11]. The study compared CP-99,994 (0.75 mg/kg iv.…”
Section: Cp-99994mentioning
confidence: 99%